Community Food Security Malasari Village, Nanggung, Bogor - Triskaprilia, Dinda; Fitriana, Hanifa Antasya; Jannah, Miftahul; Angga, Muhamad; Seviyani, Seviyani; Yulneriwarni, Yulneriwarni (Universitas Nasional Jakarta, 2025)
Food security is a fundamental aspect of human welfare, ensuring nutritional adequacy to support daily activities and enhance quality of life. This study examines food security in Malasari Village, focusing on food availability, procurement methods, and dietary patterns. Data were collected through questionnaires, observations, and documentation, then analyzed descriptively using charts, graphs, and narrative presentation. Results indicate that 56% of households rely on private agricultural land, 63% utilize home gardens for food crops, and 66% depend on private livestock for food sources. Staple food consumption predominantly consists of rice (84.06%), followed by cassava (10.14%) and bananas (5.80%). Supplementary food intake includes vegetables (24.18%), fruits (24.18%), fish (20.94%), eggs (10.7%), chicken (9.3%), nuts (9.3%), and meat (1.4%). The findings suggest that Malasari Village exhibits relatively high food security, supported by diversified local food production and accessibility. This study underscores the importance of sustainable agricultural practices and equitable food distribution to maintain community resilience.